Ikrar Aqobah Analisis Teori Komunikasi Penetrasi Sosial Terhadap Perjanjian Nabi Muhammad Dengan Suku Aus Dan Khazraj Dalam Prespektif Teori Komunikasi Penetrasi Sosial - Saiful Islam (Institut Ilmu Keislaman Zainul Hasan Genggong, 2020)
The history of the struggle of the Prophet Muhammad SAW in spreading Islamic da'wah was divided into two phases, namely the Makiah phase and the Madaniah phase, where in the Makiah phase the first method of preaching the Prophet used was the Da'wah siri (covertly) by inviting family and close friends to invite accept and embrace Islam as a religion, this kind of method continued for 3 years and was held in the house of brother Arqam, and continued propaganda openly in the Meccan community for 7 years, but the acceptance of the Meccan community for the propagation of Islam propagated by the Prophet Muhammad was not much followed or accepted, especially by the Meccan nobility, they insulted, ridiculed, boycotted even to the point of persecution and murder. From the historical story of the prophet Muhammad about the Aqobah pledge between the prophet Muhammad and the Aus tribes and the Khazraj tribe from a review of social penetration communication is